Systematics and phylogeny of the genus Caenomastax Hebard, 1923 (Orthoptera: Eumastacidae: Eumastacinae) - Cadena-Castañeda, Oscar J.; Garay, Andrea; Castañeda, Didier M.; Cardona-Granda, Juan Manuel; García, Alexander García (Zootaxa, 2016)
Eumastacinae are well-recognized because most genera feature showy colors, and because of particular morphological characteristics of the phallic complex. This orthopteran subfamily includes the genus Caenomastax, distributed in mid-elevations in the departments of Boyacá, Cundinamarca and Santander in Colombia. Three new species are described for this genus: Caenomastax similis n. sp., C. bimaculata n. sp. and C. magdalenensis n. sp. A phylogenetic analysis was performed based on morphological characters for 10 species (five ingroup and five outgroup) and 61 characters, which comprised external and genital morphology. Among the main results cast by this analysis was the proposition of Hebardomastax n. gen., within which C. atopa was previously placed, and a clarification was made on the status of the genus Zeromastax. Using the analyzed characters, an identification key is proposed for the genus.